Penciptaan Busana Pesta Malam dengan Sumber Ide Bunga Aster - Rufaydah, Indana; Wahyuningsih, Urip (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
Daisies are often referred to as stars, have many types of colors that make anyone stunned to see them. With its beauty, daisies are used as a source of ideas for the creation of a collection of evening party dresses. This study aims to determine the process of creating an evening party dress design with the source of the daisy flower idea. This research method uses the Double Diamond Design Process, which is divided into 4 stages, including discover, which is an exploration of the theme discussed in this study, namely "daisies" in which the appearance of a star-like flower figure, strands of daisies are in the shape of a circle, ranging from round to shaped like a disc. . The results obtained from applying the source of ideas to a work in the form of a moodboard. The define stage, from the results of the moodboard then makes 10 design developments. The develop stage is the stage of choosing 2 designs to be realized according to the inspiration pictures that emerged from the source of ideas to be realized in the draping pattern technique using medium size on dressfoam. The deliver stage is the process of making the details of the daisy-shaped decoration taken from the shape of the daisy crown by cutting staples according to the pattern, pressed with a satin/organza cloth to make flower crown strands and finally decorated with sequins and arranging the lace on the dress that has been given sequins and stabbed tracks. The results of the research are the finished clothes using the drapping technique and the manufacture of decorative details according to the source of ideas that apply the design principles of the center of interest and proportions.